2009
DOI: 10.1016/j.febslet.2009.07.045
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of the antifungal activity of wheat PR4 proteins

Abstract: a b s t r a c t PR4 proteins possess antifungal activity against several pathogenic fungi suggesting a pivotal role in defence reactions against plant pathogen attack. We already showed that wheatwin1, a wheat PR protein of class 4, is endowed with ribonuclease activity. In this study we produced three mutants altering the active site and performed comparative analysis with the native protein also in the presence of the ribonuclease inhibitor 5 0 -ADP. We characterized the RNA binding site and its interaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 22 publications
4
56
1
1
Order By: Relevance
“…Additionally, we selected different plant defense genes encoding pathogenesis-related proteins, which are known to play a role in the defense against infection with F. graminearum, namely, the pathogenesis-related proteins PR1 (Makandar et al, 2012), PR2, b-1,3-glucanase (Gao et al, 2013), PR4, shown to possess antifungal properties against Fusarium spp. (Bertini et al, 2009), and PR5 (thaumatinlike protein; Gao et al, 2013). As F. graminearum is known to interfere with the redox state of plant cells through the action of the mycotoxin DON, we also analyzed the expression of PEROXIDASE (PEROX) and NADPH OXIDASE (NADPHox; Desmond et al, 2008).…”
Section: Gene Expression Of Preexposed Seedlings After Treatment Withmentioning
confidence: 99%
“…Additionally, we selected different plant defense genes encoding pathogenesis-related proteins, which are known to play a role in the defense against infection with F. graminearum, namely, the pathogenesis-related proteins PR1 (Makandar et al, 2012), PR2, b-1,3-glucanase (Gao et al, 2013), PR4, shown to possess antifungal properties against Fusarium spp. (Bertini et al, 2009), and PR5 (thaumatinlike protein; Gao et al, 2013). As F. graminearum is known to interfere with the redox state of plant cells through the action of the mycotoxin DON, we also analyzed the expression of PEROXIDASE (PEROX) and NADPH OXIDASE (NADPHox; Desmond et al, 2008).…”
Section: Gene Expression Of Preexposed Seedlings After Treatment Withmentioning
confidence: 99%
“…The in vitro antifungal activity against plant pathogenic fungi has been demonstrated for some plant PR4 proteins (Zhu et al 2006;Mukherjee et al 2010). Recombinant Wheatwin1, a wheat PR protein of class 4, exhibits antifungal activity against Fusarium culmorum, F. graminearum, and B. cinerea (Caruso et al 2001;Bertini et al 2009). Purified OsPR4b and Lycoris radiata LrPR4 have antifungal activity against R. solani (Zhu et al 2006) and M. oryzae ), respectively.…”
Section: Identification and Molecular Functions Of The Pepper Pathogementioning
confidence: 99%
“…CaPR4b has strong antifungal activity against fungal pathogens. Plant PR4 proteins such as wheatwin1 (Bertini et al 2009) and OsPR4b (Zhu et al 2006) have in vitro antifungal activity against plant pathogenic fungi. CaLRR1 also binds both CaPR4b and CaHIR1 at the plasma membrane and suppresses CaPR4b-or CaHIR1-triggered pepper cell death from the apoplastic space ( Fig.…”
Section: Pepper Hypersensitive-induced Reaction Protein (Cahir1)mentioning
confidence: 99%
“…36 PR4 proteins show antifungal activity against several phytopathogenic fungi and have been demonstrated to possess ribonucleasic activity correlated to their antifungal capacity. 37,38 PR5 encodes a thaumatin-like protein which exhibits antifungal activity against snow mold and Microdochium nivale. In shoots, PR5 (WAS-3a) was induced by 2.1-fold at 72 h post MeJA treatment ( Fig.2; Supplementary Fig.S1(f)).…”
Section: Pathogenesis-related Genesmentioning
confidence: 99%
“…Briefly, sequences were quality filtered and dereplicated using the QIIME script split_libraries.py with the homopolymer filter deactivated 38 , checked for chimeras against the GreenGenes database (October 2013 release) using UCHIME ver.…”
Section: Processing Of Sequence Datamentioning
confidence: 99%